Surveying The Teaching Methods of Elephant-Foot Drum for Elementary School Students - Zhang, Yuxin; Butsamalee, Boochita (International Journal of Multidisciplinary in Management and Tourism, 2025)
This article aimed to analyze the techniques and pedagogical strategies used in teaching the elephant-foot drum to elementary students and to survey the teaching methods of elephant-foot drum for elementary school students at Shuguang Primary School. The research methodology was qualitative research, the sample were three elephant-foot drum teachers, the instrument for collecting data were interview and observation. The research results were found as follows, the elephant-foot drum was the most representative traditional instrument of the Dai ethnic group, with its history dating back to the Ming Dynasty. This instrument, shaped like an elephant’s foot, not only embodied the totem worship of the Dai ethnic group’s ancestors, but also carried the cultural concept of harmonious coexistence between humans and nature. The elephant-foot drum was divided into three sizes: large, medium, and small. When played, it was hung diagonally on the left shoulder and struck alternately with both hands. There were over ten techniques, included straight strikes, gentle strikes, and single-finger strikes. Before played, applied soft rice to the drum core can improved the tone quality. During the performance, precise control of the strength and rhythm was required. In Dai culture, the elephant foot drum was not only an important ritual instrument but also the core accompaniment for festival dances. Currently, this skill had been systematically inherited in Lincang, Yunnan Province. The teaching focused on both technique training and cultural enlightenment, through explanations of historical origins, demonstrations of playing techniques, and cultivation of rhythm sense, ensured the continuation of this intangible cultural heritage.